The Influence of the Principal's Leadership and Work Discipline on Teacher Performance in Junior High School Kuranji - Yanni A; Sufyarma M; Nellitawati; Irsyad (International Journal Of Humanities Education and Social Sciences (IJHESS), 2022)
Background of this research from the results of the author's observations the factors that affect teacher performance and how much the contribution of these factors to the performance of State Middle School teachers in Kuranji District showsrlow teacher performance and suspected to have something to do with the lack of good leadership of the school principal and teacher work discipline.The purpose of this research forget data and information about (1)Keleadership of the principal of a public junior high school in Kuranji District.(2)Dthe work discipline of State Junior High School teachers in Kuranji District, and (3) PInfluence of the principal's leadership and work discipline on the performance of State Junior High School teachers in Kuranji District.This type of research is quantitativecorrelationalwith associative type.The population of this study namelyall teachers with Civil Servants (PNS) status at Public Middle Schools in Kuranji District, totaling 142 people, with a research sample67personteachertaken by techniq proportiona lscertified random sampling. Analystisdata using multiple linear regression test processed using SPSS version 24. The research results show that 1) Leadership has a significant effect on teacher performance. The better the leadership of the principal which is shown to lead to an increase in the performance of State Middle School teachers in Kuranji District; 2) Work discipline has a significant effect on teacher performance. This shows that the better the teacher's work discipline, the better the performance of State Middle School teachers in Kuranji District; 3) Principal leadership and work discipline have a significant effect on teacher performance. This shows that the better the leadership level of the principal and the teacher's work discipline, the better the performance of State Middle School teachers in Kuranji District